Incomes Policies, Expectations and the NAIRU - Wolfgang Pollan (Austrian Institute of Economic Research (WIFO), 2008)
Since the 19960s, several countries have adopted income policies in various forms to control inflation that had been interpreted as the result of a distributional struggle between business and labour unions. Recent writings on the NAIRU, however, ignore past policy interventions in the wage and price setting system, in the formation and propagation of inflation expectations, in particular. Some of the problems inherent in such an approach are illustrated in this paper by applying the standard tools of NAIRU analysis to the Austrian economy, an economy that has been subject to a variety of policy measures.
Keywords: 330; NAIRU; incomes policies; expectations; Lucas critique; Natürliche Arbeitslosenquote; Phillips-Kurve; Schätzung; Arbeitsmarktpolitik; Wirtschaftspolitik; Österreich